2010
DOI: 10.1007/s10450-010-9259-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of low sulfur diesel fuel via adsorption: an equilibrium and kinetic study on the adsorption of dibenzothiophene onto NaY zeolite

Abstract: The adsorption of dibenzothiophene (DBT) in hexadecane onto NaY zeolite has been studied by performing equilibrium and kinetic adsorption experiments. The influence of several variables such as contact time, initial concentration of DBT and temperature on the adsorption has been investigated. The results show that the isothermal equilibrium can be represented by the Langmuir equation. The maximum adsorption capacity at different temperatures and the corresponding Langmuir constant (K L ) have been deduced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 43 publications
3
14
0
Order By: Relevance
“…Our results showed that the activation energy for the adsorption of TP on AgCeY zeolite is 13.218 kJ/mol and for the adsorption of BT is 9.302 kJ/mol, which are lower than 21 kJ/mol, suggesting the adsorptions are diffusion controlled. Similar results were obtained by others [20,[23][24][25] . Jiang and Ng [20] have studied adsorption kinetic of dibenzothiophene onto NaY Zeolite.…”
Section: Effect Of Temperature On the Adsorption Kineticssupporting
confidence: 94%
See 2 more Smart Citations
“…Our results showed that the activation energy for the adsorption of TP on AgCeY zeolite is 13.218 kJ/mol and for the adsorption of BT is 9.302 kJ/mol, which are lower than 21 kJ/mol, suggesting the adsorptions are diffusion controlled. Similar results were obtained by others [20,[23][24][25] . Jiang and Ng [20] have studied adsorption kinetic of dibenzothiophene onto NaY Zeolite.…”
Section: Effect Of Temperature On the Adsorption Kineticssupporting
confidence: 94%
“…Similar results were obtained by others [20,[23][24][25] . Jiang and Ng [20] have studied adsorption kinetic of dibenzothiophene onto NaY Zeolite. The activation energy determined to be 12.4 kJ/mol, suggesting the adsorption is mass transfer controlled.…”
Section: Effect Of Temperature On the Adsorption Kineticssupporting
confidence: 94%
See 1 more Smart Citation
“…In a recent report, the adsorption of DBT from hexadecane solution onto NaY zeolite was studied by equilibrium and kinetic adsorption measurements. [137] For adsorption to reach equilibrium, tens of hours are required and the low apparent activation energy (12.4 kJ mol…”
Section: Kinetics Of Photocatalytic Reactionsmentioning
confidence: 99%
“…We have previously reported on the use of zeolites and metal modified zeolites for the adsorptive desulfurization of liquid fuels. Liquid phase micro flow calorimetry was successfully used to determine the heat of adsorption of various adsorbate compounds (thiophene, DBT, quinoline, naphthalene) over metal modified zeolites . This study is focused on the study of the effect of metal ions on activated carbons for the removal of refractory sulfur compounds such as DBT and 4,6‐DMDBT in hexadecane as activated carbons have been reported to be good sorbents for refractory type sulfur containing compounds.…”
Section: Introductionmentioning
confidence: 99%